Evidence of parallel denitrification and nitrite oxidation in the ODZ of the Arabian Sea from paired stable isotopes of nitrate and nitrite. Issue 4 (5th November 2013) - Gaye, Birgit; Nagel, Birgit; Dähnke, Kirstin; Rixen, Tim; Emeis, Kay‐Christian
<x xml:space="preserve">Abstract</x> [1] The Arabian Sea is a major oceanic nitrogen sink, and its oxygen‐deficient zone (ODZ) extends from 150 m to 1200 m water depth. To identify the dominant transformation processes of reactive nitrogen and to quantify the amounts of nitrogen turned over in the different reactions of the nitrogen cycle, we use paired data on stable isotope ratios of nitrogen and oxygen in nitrate and nitrite measured at four near‐coastal and five open ocean stations in the Arabian Sea. We find significant nitrate reduction and denitrification between 100 m and 400 m in the open Arabian Sea, which are most intense in the eastern and northern part of the basin, and estimate that about 50% of initial nitrate is being reduced either to dinitrogen gas (denitrification) or to nitrite (nitrate reduction) in the core zone of denitrification. Nitrite accumulates in concentrations above 4 µM in the water column of the eastern and northern Arabian Sea. Large differences in isotopic ratios of nitrate and nitrite and a decoupling of their stable nitrogen and oxygen isotopes can be explained by the reoxidation of nitrite. The observed decoupling of the paired isotopes may be due to the exchange of oxygen of nitrite with oxygen from ambient water. In agreement with model estimates from the literature, about 25% of the nitrate initially reduced to nitrite is returned to the nitrate pool by nitrification in the upper and lower denitrification layer while 40% is denitrified.